Role of Interleukins and New Perspectives in Mechanisms of Resistance to Chemotherapy in Gastric Cancer - Marlena Janiczek-Polewska; Łukasz Szylberg; Julian Malicki; Andrzej Marszałek (Biomedicines, 2022)
Gastric cancer (GC) is the fourth most common cancer in the world in terms of incidence and second in terms of mortality. Chemotherapy is the main treatment for GC. The greatest challenge and major cause of GC treatment failure is resistance to chemotherapy. As such, research is ongoing into molecular evaluation, investigating mechanisms, and screening therapeutic targets. Several mechanisms related to both the tumor cells and the tumor microenvironment (TME) are involved in resistance to chemotherapy. TME promotes the secretion of various inflammatory cytokines. Recent studies have revealed that inflammatory cytokines affect not only tumor growth, but also chemoresistance. Cytokines in TME can be detected in blood circulation and TME cells. Inflammatory cytokines could serve as potential biomarkers in the assessment of chemoresistance and influence the management of therapeutics in GC. This review presents recent data concerning research on inflammatory cytokines involved in the mechanisms of chemoresistance and provides new clues in GC treatment.